2002
DOI: 10.1074/jbc.m201178200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cell-Cell Interactions in the Rapid Stimulation of Cas Tyrosine Phosphorylation and Src Kinase Activity by Transforming Growth Factor-β1

Abstract: Transforming growth factor-␤ (TGF-␤) regulates a wide range of physiological and pathological cellular processes, including cell migration, mesenchymal transition, extracellular matrix synthesis, and cell death. Cas (Crk-associated substrate, 130 kDa), an adaptor protein localized at focal adhesions and stress fibers, is also known to have important functions in cell migration and the induction of immediate-early gene expression. Here, we report that a rapid and transient tyrosine phosphorylation of Cas is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 69 publications
3
32
0
Order By: Relevance
“…EGFR transactivation then induces c-Fos/c-Jun expression via the ERK signaling cascade. E-cadherin-mediated cell-cell interactions are also required for this event, similar with the effect of TGF-b on c-Src activation in epithelial cells, previously reported by us (Kim and Joo, 2002).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…EGFR transactivation then induces c-Fos/c-Jun expression via the ERK signaling cascade. E-cadherin-mediated cell-cell interactions are also required for this event, similar with the effect of TGF-b on c-Src activation in epithelial cells, previously reported by us (Kim and Joo, 2002).…”
Section: Introductionsupporting
confidence: 58%
“…Cell-cell interactions via E-cadherin involve extracellular binding and intracellular anchorage to the actin-based cytoskeleton (Takeichi, 1991). Moreover, we showed previously that E-cadherin expression and cell-cell interaction mediated by it are important for TGF-b-induced c-Src activation (Kim and Joo, 2002). Hence, we investigated the effects of E-cadherin expression and cell-cell interactions mediated by it on EGFR transactivation.…”
Section: Stimulation Of Egfr Transactivation By Tgf-b1mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating data indicate that these pathways have been implicated in a number of phenomena associated with tumor promotion (6). The Src kinase pathway is involved in this early TGF-␤ signaling (3,7). The Smad signaling pathway constitutes a main signal transduction route downstream of TGF-␤ receptors (8).…”
mentioning
confidence: 99%
“…One of the factors regulating the metastatic process is considered to be transforming growth factor-␤ (TGF-␤), which is a multifunctional cytokine that elicits numerous cellular effects pertinent to the metastatic process (1). TGF-␤ regulates a wide range of physiological and pathological cellular processes, including cell growth, differentiation, invasion, migration, mesenchymal transition, extracellular matrix synthesis, and cell death in many cell types including ovarian cancer cells (3). Recent data demonstrated that TGF-␤ specifically stimulates up-regulation of uPA mRNA and protein in certain types of neoplastic cells (1).…”
mentioning
confidence: 99%